Quality Evaluation and Optimization Methods of Universities Physical Education Teaching in Henan Province, China - Cui, Yangyang (International Journal of Social Sciences and Public Administration, 2024)
This study aims to determine the quality evaluation and optimization methods of physical education teaching in the universities in Henan Province, China, in order to formulate a strengthening development plan. Through high-quality physical education teaching, students can master scientific sports skills and methods, enhance their physical fitness, and provide healthy protection for their study and life.This study was conducted in five universities in Henan Province, China, namely: Henan University, Luoyang Normal University, Zhengzhou University, Henan University of Science and Technology University and Zhengzhou Sias University. In these universities, physical education is a compulsory course for first-year and second-year students. The students were the respondents. They were selected using random sampling techniques. This study used simple random sampling, which means that each possible sample drawn from the population has the same probability of being drawn.